2009
DOI: 10.1080/02701960902911281
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Gerontology Courses: How Do They Measure Up?

Abstract: This study compared Web-based and lecture-based Gerontology and Psychology of Aging courses in terms of student performance, demographic and academic characteristics of students enrolled in the courses, and extent to which these characteristics differentially predicted outcomes of learning in the two course types. Participants for this study were 289 undergraduate students who completed a Psychology of Aging or Gerontology course, taught in either a Web-based or lecture-based format. Evaluation of student perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There is evidence that e-learning is already used by dentists, nurses, social workers and physiotherapists internationally, [49][50][51][52] although evidence for its effectiveness is lacking. The advantages of e-learning for postgraduate medics such as flexibility in terms of engagement, and the use of e-portfolios for CPD and formal evaluation/revalidation, are shared by these other professional groups.…”
Section: Other Healthcare Professionals Working With Older Peoplementioning
confidence: 99%
“…There is evidence that e-learning is already used by dentists, nurses, social workers and physiotherapists internationally, [49][50][51][52] although evidence for its effectiveness is lacking. The advantages of e-learning for postgraduate medics such as flexibility in terms of engagement, and the use of e-portfolios for CPD and formal evaluation/revalidation, are shared by these other professional groups.…”
Section: Other Healthcare Professionals Working With Older Peoplementioning
confidence: 99%
“…Many forms of asynchronous distance learning can be made available to be accessed at any time of day, allowing the learners to use their leisure time to advance their knowledge and learn at their own speed. Notably, research has shown that learning scores of individuals taking distance or web-based courses are not significantly different than those taking lecture-based courses (Hills, Brallier, Palm, & Graham, 2009;Palm, Brallier, Gilbert, & Darrone, 2007). Synchronous distance learning allows information to be broadcast simultaneously to a wide range of participants at many locations, increasing the number and variety of programs available to a learner as well as expanding the size of the potential audience for the presenter.…”
Section: Benefits Of Distance Education For Continuing Medical Educationmentioning
confidence: 98%